The color purple - Spielberg, Steven, 1946-; Meyjes, Menno; Goldberg, Whoopi, 1950-; Glover, Danny; Caesar, Adolph, 1933-1986; Walker, Alice, 1944-; Jones, Quincy, 1933-2024; Amblin Entertainment (Firm); Warner Home Video (Firm) (Burbank, CA : Warner Home Video, 2003)
The story of Celie, a poor black woman from the south, whose friendship with two women helps her overcome the brutality of her father and husband.
Based on the novel by Alice Walker.
Originally released as a motion picture in 1985.
Features: interactive menus, awards notes, trailer, scene access, four documentaries, storyboard and photo galleries.
Director of photography, Allen Daviau; production design, J. Michael Riva; film editors, Michael Kahn, Scott Hansen; music, Quincy Jones.
Whoopie Goldberg, Danny Glover, Adolph Caesar, Margaret Avery, Rae Dawn Chong, Oprah Winfrey.
MPAA rating: PG-13.
Keywords: Walker, Alice, -- 1944- -- Film and video adaptations; African American women -- Drama; Dysfunctional families -- Drama; Video recordings for hard of hearing people; Based on the book; Feature films